Attitude Semantics - Ciardelli, Ivano (Proceedings of the Amsterdam Colloquium, 2019)
Many recent theories treat indicative conditionals as restricted necessity modals. I discuss two problems for this view. First, indicative conditionals do not behave like necessity modals in embedded contexts, e.g., under ‘might’ and ‘probably’: in these contexts, conditionals do not contribute a universal quantification over epistemic possibilities. Second, when we assess the probability of a conditional, we do not assess how likely it is that the consequent is necessary given the antecedent, but how likely it is that it is true given the antecedent. I propose an account which predicts the embedding behavior of conditionals under modals and the way we assign probabilities to conditionals. The account is based on the idea that the semantics of conditionals involves only a restriction of the relevant epistemic state, and no quantification over epistemic possibilities. The relevant quantification is contributed by an attitude parameter in the semantics, which is shifted by epistemic modals. If the conditional is asserted, the designated attitude is acceptance, which contributes a universal quantifier, producing the overall effect of a restricted necessity modal.